1977
DOI: 10.1097/00000658-197707000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Regional Pancreatectomy

Abstract: Eighteen patients are reported who have had a regional pancreatectomy. The pancreatic segment of portal vein was excised with en bloc total pancreatectomy and regional lymph node dissection in all 18. Venous repair was by end-to-end anastomosis without a graft. Five of the 18 also had various arterial resections and reconstructions. Sixteen of the 18 had been explored and deemed nonresectable elsewhere. This operation has doubled the resectability rate in this institution. The 30-day operative mortality rate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 220 publications
(37 citation statements)
references
References 12 publications
0
37
0
Order By: Relevance
“…Portal vein resection represents therefore the last option for patients with locally advanced disease to receive potential curative surgery [15, 1012] after diagnosis of PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…Portal vein resection represents therefore the last option for patients with locally advanced disease to receive potential curative surgery [15, 1012] after diagnosis of PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major controversies regarding radical resection is the role of total pancreatectomy for ductal adenocarcinomas. As the results of Whipple procedures were disappointing, some surgeons converted to total pan createctomy [3][4][5], When the study commenced in 1973, we advocated total pancreatectomy as the treatment of choice for cancer of the pancreas. This seemed justified because of the pos sible spread to the left of the mesenteric vessels by cancer situated in the head of the pancreas; the procedure achieved a wider lymphadenectomy as well as ensuring removal of multicentric malignant foci.…”
Section: Discussionmentioning
confidence: 99%
“…Nakao et al [19]found histopathological extrapancreatic nerve plexus invasion in 14 of 30 patients with carcinoma of the body and tail of the pancreas. Pancreatic cancer is also characterized by the high frequency of intrapancreatic neural invasion (75–100%) [14, 15, 17, 18, 20]. Therefore to erradicate pancreatic cancer a complete plexus dissection must be performed around the superior mesenteric artery, common hepatic artery and coeliac axis including soft tissue removal.…”
Section: Neural and Soft Tissue Invasion:vascular Involvementmentioning
confidence: 99%